Analisis Risiko Sistem Informasi Pada RSIA Eria Bunda menggunakan Metode FMEA - puja hanifah; Jarot S Suroso (Jurnal Komputer Terapan, 2020)
Technology that is rapidly developing in the IT field is an important and complementary component in processing data and information in an organization. There are many risks that may occur that will threaten the organization.  Therefore, it is necessary to carry out risk management against threats to information system security and risk assessment. There are many methods that can be used in managing and assessing risk. One of them is the FMEA (Failure Mode and Effect Analysis) method. In this study, taking a case study at RSIA Eria Bunda. As an industry engaged in the health sector, RSIA Eria Bunda needs to maintain the confidentiality of information regarding patient data, doctors, medicines, and other staff from threats that may pose risks that can harm the industry. Where the research objective is to find out how the level of risk that occurs in the information system and provide mitigation solutions to RSIA Eria Bunda. There are ten stages in risk identification and assessment using the FMEA method. So from the results of this study there is one activity with a high category, 6 activities in the medium category and nineteen activities with a low category